EVALUASI PENERAPAN KOLAM PARSIAL DAN PENGARUH GAYA PASANG SURUT BERDASARKAN POLA SIRKULASI, UMUR AIR, BESI TERLARUT (Fe) dan TSS DI UNIT REKLAMASI TERANTANG, DESA TERANTANG, KABUPATEN BARITO KUALA, KALIMANTAN SELATAN - Hasibuan, M. Istiqlal; Riduan, Rony; Khair, Riza Miftahul; Mazaya, Gusti Ihda (Prodi Teknik Lingkungan Fakultas Teknik Universitas Lambung Mangkurat, 2025)
Swamp land in Terantang Village, Barito Kuala Regency, South Kalimantan has the potential to be utilized if managed optimally. Sour swamp land needs to be managed by the reclamation process. However, the high accumulation of toxic iron (Fe) becomes an obstacle in optimizing the reclamation process. The two-way flow system with the help of tidal ponds in the reclamation channel used still needs further evaluation to find out how effective the washing of toxic materials is. The main factors that influence the most are tidal events and partial pond function. The use of Environmental Fluids Dynamic Code (EFDC) software with simulation based on the data obtained is estimated to be able to solve the existing problems. This research was conducted in primary, secondary and tertiary reclamation channels with several stages. The first stage is to identify the hydrodynamic conditions and water quality in the Terantang unit reclamation channel. The second stage is the preparation and testing of the model. The second stage is the preparation and testing of the model. The last stage is model simulation on flow pattern, water age, accumulation of iron (Fe) concentration and accumulation of TSS concentration in 3 scenarios. The scenarios consist of simulating the hydrodynamic aspects of current movement and water age and 2 simulation scenarios of the water quality aspect on the accumulation of iron (Fe) concentration and TSS concentration by paying attention to the partition coefficient and without the partition coefficient. Simulations were carried out using the primary, secondary and 5 tertiary channel representative model data. The simulation results show that the application of channel tidal forces and partial pool utilization is still not running well. This happened based on the simulation results on the hydrodynamic and water quality aspects, showing that the water washing process still reached 60% with the water age reaching 3 days. The tidal force of the water is not able to reach the end of the channel and the tide pattern has not yet reached the end of the channel but has receded.